(untitled) (International Journal of Physiotherapy, 2019)
Background: Plantar fasciitis is the most common cause of inferior heel pain resulted from repeated trauma leading to a microscopic tear in the plantar fascia. There is a need to study the non-invasive nature of low-level laser therapy in reducing pain and enhance healing. Therefore the study aimed to find out the efficacy of low-level laser therapy in plantar fasciitis. Methods: The study design is a pre-post experimental design. Thirty patients(21 females & 9 males) with plantar fasciitis who fulfilled the inclusion criteria participated in the study. Baseline parameters using musculoskeletal ultrasonogram of the plantar fascia, numerical pain rating scale, ankle joint mobility testing and foot and ankle ability measure questionnaire were recorded. Subjects in the control group received ultrasonic therapy, while the experimental group received irradiation of Low-Level Laser Therapy (LLLT) for two weeks comprising 12 sessions and the above-specified outcome measures were re-evaluated after two weeks. Results: The results showed significant improvement in pain severity (p<0.04) and ankle dorsiflexion range of motion (p<0.00) and ankle ability measure but no significant change in plantar fascia thickness following low-level laser therapy was observed. A positive correlation (r=0.9) was found between plantar fascia thickness and post foot and ankle ability measure-ADL scores (p=0.02). Conclusion: The findings suggest that low-level laser therapy helps in pain reduction and improving range of motion in plantar fasciitis with minimal effect on the thickness of plantar fascia.